Implementasi Penerapan Metode Kerja Kelompok Dalam Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran IPS Di SD Inpres Kampus IKIP Kota Makassar - Shasliani Shasliani (Universitas Negeri Makassar, 2021)
This study aims, namely, 1) to determine how the method of group work in social studies subjects at SD Inpres Kampus IKIP, 2) to determine whether the technique of group work affects improving student learning outcomes in social studies topics. The research was conducted using a quantitative statistical approach. The data collection techniques used were observation, questionnaires, interviews, and documentation. The data were analyzed using descriptive statistical analysis and quantitative statistical analysis. Based on the research results, it can be seen that 1) the application of group work methods in social studies subjects at SD Inpres Kampus IKIP Makassar city is in the